Analyzing the antibacterial ability of green okra fruit (Abelmoschus esculentus L. Moench.) extract at several concentrations against Staphylococcus aureus: an experiment study - Lestari, Sri; Safitri, Rizkiya Agnes; Cholid, Zainul; Dharmayanti, Agustin Wulan Suci (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: The common bacteria found in infected root canals are Gram-positive bacteria such as Staphylococcus aureus (20%). The bacterial infection can spread to the periapical tissues causing periapical lesions. Pulp necrosis, the cause of periapical lesions, requires root canal treatment. Ethylenediaminetetraacetic acid (17% EDTA) is one of the irrigants that can be used for root canal treatment however, 17% EDTA has a low antibacterial effect. The green okra fruit extract contains antibacterial properties that can inhibit the growth of bacteria. This study aims to analyze the antibacterial ability of green okra fruit extract at concentrations of 12.5, 25, 50, and 100% against S. aureus using a negative and positive control. Methods: This type of research was an in-vitro laboratory experiment with a posttest-only control group design. The antibacterial test using the disc diffusion method consisted of six groups: green okra fruit extract concentrations of 12.5, 25, 50, 100, and 17% EDTA (positive control), and aquadest (negative control). Antibacterial ability is indicated by the clear zone produced around the disc paper. Results: The average diameters of the inhibition zone were the green okra fruit extract concentrations of 12.5% (12.14), 25% (14.89), 50% (18.53), 100 (21.1), and 17% EDTA (22.08 mm), and 0 mm for aquadest. The results were analyzed using the Mann-Whitney test and showed a significant difference between all research groups (p<0.05). Conclusion: The antibacterial ability of green okra fruit extract (Abelmoschus esculentus L. Moench) against S. aureus increased with increasing concentrations, but remained lower than the antibacterial ability of 17% EDTA.